PARLIEMENT’S PERFORMANCE IN MONITORING THE DEVELOPMENT OF THE DIITRIC TALAUD ISLANDS - MURAHANG, TOPIK; ROMPAS, Welson Y (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACTIn accordance with the mandate of the ACT.No. 32 of 2004, ACT.No. 27 in 2009, and PP.No.16 in 2010 that the LEGISLATORS have the functions, duties and authority to conductsurveillance against the implementation of regional development. But in many of thecommon phenomenon of LEGISLATIVE oversight showed that the maximum so that theimplementation of regional development programmes are frequent irregularities and abuses.With respect to these problems then this research aims to find out how the performance ofLEGISLATIVE KabupatenTalaud the supervision of regional development.This study uses qualitative methods. Data sources informants in research is takenfrom the pimpinananggota elements of the Talaud Islands Regency DPRD Commission II (5people) and Chairman of the local government agencies (DinasBadan) partner CommissionII (5 persons), totaling 10 people. Primary data collection using interview techniques. Whiledata analysis using qualitative analysis techniques, interactive model of the Miles andHubernan.The research results obtained representation: (1) supervision of the DPRD TalaudIslands Regency in the determination of the kebijakanprogramproyek regional developmentimplemented through work meetings of Commission II with every regional governmentagency partners in order to conduct the deliberations of the draft programproyek which willbe included in the BUDGETS; (2) supervision of the Talaud Islands RegencyLEGISLATORS against the implementation of the regional development programproyek isimplemented through work meetings and hearings of Commission II with partner agenciesin order to discuss the implementation of the liability report programproyek, as well asthrough the work of Commission II's visit to the site of programproyek development.Based on the analysis of the data shows that supervision of the DPRD TalaudIslands Regency of regional development in principle have been conducted with quiteeffective, efficient, transparent, and accountable. Therefore drawn the conclusion that theperformance of the Talaud Islands Regency DPRD in monitoring regional development isquite goodConclusion based on the results of the study suggested that to improve the performance ofLEGISLATIVE supervision in Talaud Islands Regency regional development then it isrecommended that: (1) the Commission II (areas of development) the DPRD to be filled in bythe people who have competence in the field of administrasimanajemen development; (2) theDPRD members personnel placed on Commission II (areas of development) to be giventraining in the field of administrasimanajemen development in the early period; (3) theworking relationship of Commission II (development areas) with a partner agencies shouldbe more intensive, especially through work meetings and hearings.Keyword: Performance Of Legislators; Supervision Of Regional Development.